Quorum Sensing: An Under-Explored Phenomenon in the Phylum Actinobacteria - Polkade, Ashish V.; Mantri, Shailesh S.; Patwekar, Umera J.; Jangid, Kamlesh (Frontiers in Microbiology, 2016)
Quorum sensing is known to play a major role in the regulation of secondary metabolite production, especially antibiotics, and morphogenesis in the phylum Actinobacteria. Although it is one of the largest bacterial phylum, only 25 of the 342 genera have been reported to use quorum sensing. Of these, only nine have accompanying experimental evidence; the rest are only known through bioinformatic analysis of gene/genome sequences. It is evident that this important communication mechanism is not extensively explored in Actinobacteria. In this review, we summarize the different quorum sensing systems while identifying the limitations of the existing screening strategies and addressing the improvements that have taken place in this field in recent years. The γ-butyrolactone system turned out to be almost exclusively limited to this phylum. In addition, methylenomycin furans, AI-2 and other putative AHL-like signaling molecules are also reported in Actinobacteria. The lack of existing screening systems in detecting minute quantities and of a wider range of signaling molecules was a major reason behind the limited information available on quorum sensing in this phylum. However, recent improvements in screening strategies hold a promising future and are likely to increase the discovery of new signaling molecules. Further, the quorum quenching ability in many Actinobacteria has a great potential in controlling the spread of plant and animal pathogens. A systematic and coordinated effort is required to screen and exploit the enormous potential that quorum sensing in the phylum Actinobacteria has to offer for human benefit.